Evaluation of the Effect of Oral Corticosteroid Treatment on Clinical Course, Hospitalization and Mortality in COVID-19 Patients - Umay Balcı; Figen Sarıgül; Derya Seyman; Alper Tahmaz; Ayşegül Seremet Keskin; Kübra Demir Önder; Hande Berk; Ulku User; Filiz Kizilates (Van Tıp Dergisi, 2022)
INTRODUCTION: It has been reported that short-term and low-dose intravenous corticosteroids prevent the progression of the disease and reduce mortality during the hyperinflammation period caused by the virus in COVID-19 disease. The aim of our study is to evaluate the clinical course, hospital readmission and mortality rates of patients with mild to moderate COVID-19 pneumonia, who do not need oxygen and for whom we started outpatient corticosteroid treatment. METHODS: Patients over the age of 18 who applied to our hospital with the diagnosis of mild-to-moderate COVID-19 pneumonia and were treated with outpatient oral systemic corticosteroid were included in the study.Inclusion criteria were pneumonia finding consistent with mild to moderate COVID-19 involvement in lung computerized tomography, seven days or more from symptom onset, and oxygen saturation of 93 and above. The patients were given dexamethasone 8 milligrams (mg) methylprednisolone 32 mg, methylprednisolone 40 mg as oral systemic corticosteroid. RESULTS: The median age (min-max) of the patients was 49.24 (22-91), and 60% of them were male. The median steroid duration was 6.6 (1-10) days. Due to ongoing symptoms, 56% of the patients were admitted to the hospital again, 12% were hospitalized due to clinical and laboratory deterioration, the intensive care hospitalization rate was 3% and the mortality rate was 2% (2/100). DISCUSSION AND CONCLUSION: As a result, the effectiveness of oral corticosteroids on mortality and morbidity has not been demonstrated in mild to moderate COVID-19 pneumonia. Well-designed randomized controlled studies are needed on this subject.